Modelling of Material Removal Rate in ultrasonic drilling of alumina ceramic by Fuzzy Logic. (4th September 2009) - Gill, Simranpreet Singh; Singh, Jagdev
Ultrasonic machining is a mechanical material removal process used to erode holes and cavities in hard and brittle workpieces. The present paper demonstrates the use of a Adaptive Neuro-Fuzzy Inference System (ANFIS) technique of fuzzy based systems to simulate the Material Removal Rate (MRR) in ultrasonic drilling of alumina ceramic. The model is based on two input signals; depth of penetration and time for penetration. The performance of the model is validated by comparing the predicted results with the actual practical results obtained by conducting the corroboration experiments. The knowledge and understanding thus obtained can be used to improve the efficiency of these processes.